517 The firefighter multicenter cancer cohort study: framework development and testing. (24th April 2018) - Burgess, JL; Caban-Martinez, A; Fent, K; Grant, C; Griffin, SC; Solle, N; Jeong, KS; Zhao, J; Littau, S; Jacobs, E; Jahnke, S; Horn, G; et al.
Abstract : Introduction: Recent epidemiologic studies in the United States have demonstrated excess mortality rates for cancer in firefighters compared with the general population. Firefighters are exposed to multiple carcinogens in the workplace through skin contamination and inhalation. However, we currently do not understand which individual exposures are responsible for cancer in firefighters, the mechanisms by which these exposures cause cancer, or effective means of reducing exposures. Development of a large multicenter firefighter cancer prospective cohort study will address these needs, but the framework for such a study needs to be first developed and tested among a smaller initial set of fire service partners. Methods: The study is harmonising existing firefighter cohort studies in Arizona and Florida, and expanding to include the Boston Fire Department and volunteer and combination fire departments. The study framework components include an Oversight and Planning Board (OPB), a Data Coordination Centre (DCC), an Exposure Assessment Centre (EAC) and a Biomarker Analysis Centre (BAC). Results: The OPB is providing oversight of the study through collaboration with fire service organisations and government agencies. The DCC is developing standardised participant survey data collection tools and analysis protocols sufficient to address the short- and long-term study objectives as well as linkage with long-term outcome data including cancer development. The EAC is developing a carcinogen exposure matrix using self-reported and quantitative exposure measurements to provide improved occupational exposure data for comparison with epigenetic outcomes and eventual cancer outcomes. The BAC is carrying out pilot studies of epigenetic markers of carcinogenic effect and cancer risk comparing firefighters with a range of cumulative exposures and non-firefighter controls. Conclusion: A framework is being established for the subsequent development of a large multicenter cohort study of cancer in the fire service; advance our understanding of firefighter exposures to carcinogens; and help identify biomarkers of carcinogen effect and cancer risk.